IMPLEMENTASI ASUHAN KEBIDANAN KOMPREHENSIF DI DUSUN NGLANO, PANDEYAN, TASIKMADU, KARANGANYAR - Putriyana Putriyana; Ana Wigunantiningsih; Siskana Dewi Rosita (Jurnal Ilmiah Maternal, 2023)
Indonesia's health profile in 2020 showed a maternal mortality rate of 4,627 deaths. This number shows an increase compared to 2019 of 4,221 deaths. Meanwhile, the number of AKB deaths in 2020 is expected to be 20,266. One of the efforts to accelerate the decline of MMR and AKB is by carrying out continuous care, or continuity of care (CoC), namely obstetric services carried out starting from pregnancy, childbirth, puerperium, and newborns. During the COVID-19 period, where there are restrictions on maternal and neonatal services, it is hoped that mothers and babies will continue to get services, essential risk factors can be recognized early, and they will get access to emergency relief. Research uses a descriptive-qualitative design with a case study approach. The subject of the study was a 35-year-old G2P1A0 mother who was 35+3 weeks pregnant.The data used is in the form of primary and secondary data. The results of the study were obtained by mothers who got care in accordance with standards both when they were ANC, INC, PNC, BBL, and KB. So long as there are no complications found in the mother or baby, the PEB experienced by the mother at the end of pregnancy gets the appropriate care and there are no problems. The results of the analysis found that there was no gap between theory and practice or the upbringing received by the mother. Key words: implementation, midwifery care, and comprehensive care.